2005
DOI: 10.1002/ejic.200400414
|View full text |Cite
|
Sign up to set email alerts
|

High‐Field EPR Study of Frozen Aqueous Solutions of Iron(III) Citrate Complexes

Abstract: Keywords: High-field EPR spectroscopy / Iron / Coordination chemistry / Citrate ligand / Tripodal ligand / Spin crossover High-field electron paramagnetic resonance spectra have been measured for frozen aqueous solutions of Fe III citrate at acidic and neutral pH values. At high fields (up to 12 T) and high frequencies (95, 190 and 285 GHz), fine-structure peaks due to resonance between Kramers doublets (±1/2, ±3/2, ±5/ 2) of an S = 5/2 species can be observed when the experiments are performed at high tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 62 publications
1
9
0
Order By: Relevance
“…Finally, these fine structure parameters are typical of mononuclear, high-spin iron­(III) sites. Such species have been extensively characterized by EPR, most often at X-band (∼9 GHz), but also at higher frequencies . To facilitate the comparison of these results with our study we have recorded, for a neat powder sample of 1 , several low-temperature X-band EPR spectra; see Figure S4.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, these fine structure parameters are typical of mononuclear, high-spin iron­(III) sites. Such species have been extensively characterized by EPR, most often at X-band (∼9 GHz), but also at higher frequencies . To facilitate the comparison of these results with our study we have recorded, for a neat powder sample of 1 , several low-temperature X-band EPR spectra; see Figure S4.…”
Section: Resultsmentioning
confidence: 99%
“…Such species have been extensively characterized by EPR, most often at X-band (∼9 GHz), but also at higher frequencies. 32 To facilitate the comparison of these results with our study we have recorded, for a neat powder sample of 1, several low-temperature X-band EPR spectra; see Figure S4. Moreover, we also present some representative theoretical spectra predicted for 1, see Figure S5, and their rationalization, see Figures S6 and S7.…”
Section: Development Of the Mpmae-h Ligand And Thementioning
confidence: 87%
“…The values of D 0 ) 0.32 cm -1 and λ ) 0.31 are fairly typical for tris chelation to oxygen or nitrogen bidentate ligands to iron. 56,57 Reviewing the simulation parameters in Table 1, the most visible trend is that of the increase in the median value of λ as the number of coordinated catecholates increases. The [Fe(cat) 3 ] 3complex is expected to have a trigonally distorted octahedral geometry for which the median value of λ ) 0.31 is quite reasonable.…”
Section: Resultsmentioning
confidence: 99%
“…The available crystal structures for ferric citrate complexes indicate that the hydroxyl proton is lost when citrate coordinates iron(III) 20, 22 and definitive evidence that this group exists in the alkoxide form in aqueous ferric citrate complexes was obtained utilizing high-field EPR spectroscopy. 33 It is important to note that the high-field EPR study was carried out at iron : citrate molar ratios of 1 : 20 and under these conditions it was unequivocally demonstrated that the species present in solution is the mononuclear dicitrate complex.…”
Section: Discussionmentioning
confidence: 99%